Internet of things security : challenges, advances and analytics - Patel, Chintan; Doshi, Nishant (CRC Press, Taylor & Francis Group, 2019)
This book focuses on the use of Elliptic Curve Cryptography with different authentication architectures and authentication schemes using various security algorithms to secure the Internet of Things. It also include mathematics from basic level to advance level required for security--